Discovery of novel potent ΔF508‐CFTR correctors that target the nucleotide binding domain. Issue 10 (27th August 2013) - Odolczyk, Norbert; Fritsch, Janine; Norez, Caroline; Servel, Nathalie; da Cunha, Melanie Faria; Bitam, Sara; Kupniewska, Anna; Wiszniewski, Ludovic; Colas, Julien; Tarnowski, Krzysztof; Tondelier, Danielle; Roldan, Ariel; et al.
<x xml:space="preserve">Abstract</x> The deletion of Phe508 (ΔF508) in the first nucleotide binding domain (NBD1) of CFTR is the most common mutation associated with cystic fibrosis. The ΔF508‐CFTR mutant is recognized as improperly folded and targeted for proteasomal degradation. Based on molecular dynamics simulation results, we hypothesized that interaction between ΔF508‐NBD1 and housekeeping proteins prevents ΔF508‐CFTR delivery to the plasma membrane. Based on this assumption we applied structure‐based virtual screening to identify new low‐molecular‐weight compounds that should bind to ΔF508‐NBD1 and act as protein–protein interaction inhibitors. Using different functional assays for CFTR activity, we demonstrated that in silico‐selected compounds induced functional expression of ΔF508‐CFTR in transfected HeLa cells, human bronchial CF cells in primary culture, and in the nasal epithelium of homozygous ΔF508‐CFTR mice. The proposed compounds disrupt keratin8‐ΔF508‐CFTR interaction in ΔF508‐CFTR HeLa cells. Structural analysis of ΔF508‐NBD1 in the presence of these compounds suggests their binding to NBD1. We conclude that our strategy leads to the discovery of new compounds that are among the most potent correctors of ΔF508‐CFTR trafficking defect known to date.